Professional development teacher to improve skills of science process and creativity of learners - Muhammad Sholahuddin Amrulloh; Andarula Galushasti (Intelektual Pustaka Media Utama, 2022)
This qualitative research emphasized learning strategies in the process of full engagement by students and discovering the implementation of learning, science process skills, and learners' creativity. The selection of contextual teaching and learning methods due to teachers having a role more in strategy affairs while learners were more focused on self-actualization of practice in their groups. Here, there was an interaction between teachers and learners to complement each other. The participant was student of class five Elementary School/Madrasah Ibtidaiyah Ma'arif 37 Sunan Kalijogo, Ambulu, Jember Regency, Indonesia. Methods of data collection were interviews, observations, and documentation. Data collection was related to natural science subjects. The study results showed the procedures for implementing contextual teaching and learning in natural science subjects. Applying contextual teaching and learning methods was very effective in natural science subjects. The findings of this study showed that improving the quality of learning and learning support facilities can realize the ability of competence of students and teacher professionalism.